IMPLIKASI EKSISTENSI UU PERTAMBANGAN DALAM UPAYA PENYELESAIAN PERMASALAHAN PERTAMBANGAN ILEGAL (Studi Kasus Korupsi Tata Niaga Komoditas Timah di IUP PT Timah Tbk) - Rajwa Khaicirinu Riyanto; Dian Istimeisyah; Muhammad Gaung Syah Arjuna; Raisha Tiara Hasnakusumah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Mining without a permit (PETI) is basically a crime against state assets in the form of theft of minerals, where the crime is ignoring the provisions of mining procedures. The PT Timah corruption case resulted in losses for Timah as one of the largest natural resources in Indonesia and also high environmental losses. On the regulatory side, mining without a permit (PETI) or illegal mining certainly violates applicable law in Indonesia. Therefore, the author conducted studies and research regarding how legal violations are caused by illegal mining. The writing method that the author uses is qualitative with a normative juridical approach, namely a statutory approach and a case study approach. Based on the results obtained from the literature, the author can conclude that Unlicensed Mining (PETI)/Illegal Mining can cause losses to the country's natural wealth, high losses to the environment where living creatures live, and large losses to various manufacturing industries, including automotive, electronics , and construction. In this case, the government drafted Law Number 3 of 2020 as an amendment to Law No. 4 of 2009 concerning Mineral and Coal Mining which plays a role in increasing sanctions against perpetrators of mining activities.